Carbohydrate Self‐Assembly at Surfaces: STM Imaging of Sucrose Conformation and Ordering on Cu(100). (23rd May 2019) - Abb, Sabine; Tarrat, Nathalie; Cortés, Juan; Andriyevsky, Bohdan; Harnau, Ludger; Schön, J. Christian; Rauschenbach, Stephan; Kern, Klaus
Abstract: Saccharides are ubiquitous biomolecules, but little is known about their interaction with, and assembly at, surfaces. By combining preparative mass spectrometry with scanning tunneling microscopy, we have been able to address the conformation and self‐assembly of the disaccharide sucrose on a Cu(100) surface with subunit‐level imaging. By employing a multistage modeling approach in combination with the experimental data, we can rationalize the conformation on the surface as well as the interactions between the sucrose molecules, thereby yielding models of the observed self‐assembled patterns on the surface. Abstract : Süße Oberfläche : Mittels präparativer Massenspektrometrie und Rastertunnelmikroskopie gelang es, das Disaccharid Sucrose auf einer Cu(100)‐Oberfläche mit einer Auflösung auf Untereinheiten‐Ebene abzubilden. Mithilfe eines mehrstufigen Modellierungsansatzes konnte die Konformation des Disaccharids an der Oberfläche sowie die Wechselwirkungen zwischen den Sucrosemolekülen abgeleitet werden.